Follicular Cell Hyperplasia (Goitre), Adenoma and Adenocarcinoma of the Thyroid Gland in Fourlined Terapon (Pelates quadrilineatus) Clinical and Histopathological Study: 2022-2023 - Rahmati-Holasoo, Hooman (Journal of fish diseases, 2025)
© 2024 John Wiley & Sons Ltd.